How norms concerning maternity, femininity and cisgender increase stress among lesbians, bisexual women and transgender people with a fear of childbirth. (February 2021) - Malmquist, Anna; Wikström, Johanna; Jonsson, Louise; Nieminen, Katri
Abstract: Objective: To explore and describe norms concerning maternity, femininity and cisgender in lesbian and bisexual women and transgender people (LBT) assigned female at birth, with an expressed fear of childbirth (FOC). Design: Semi-structured interviews were conducted with self-identified LBT people with an expressed FOC. Participants: 17 self-identified LBT people participated. 15 had an expressed FOC, and two were non-afraid partners. Findings: Participants described how their FOC was related to ideals of "the primal woman", including ideals of a natural birth. They also described stress in relation to expectations of gaining a feminine-coded body during pregnancy and of being related to as feminine women. Key conclusions: Maternity ideals, and the ideal of the "natural" birth, can be particularly stressful on those who fear childbirth. Norms concerning femininity and cisgender can contribute to FOC among those who do not comfortably conform with feminine body ideals or feminine gender expressions. Implication for practice: Treatments of FOC must be designed to acknowledge whether and how norms concerning maternity, femininity and cisgender affect the individual's FOC.